The impact of direct resin facets on periodontal tissue: literature review (Research, Society and Development, 2022)
The growing search for excellent treatments that meet the demands of dental aesthetics, combined with advances in dental materials, favored the evolution of dental veneers that result in a satisfactory aesthetics with greater preservation of the dental element, response to less wear for inclusion of the material. restorative, but the indiscriminate use of the veneer preparation technique can cause damage to the periodontal tissue. Thus, in order to gather and summarize scientific knowledge on the subject, this study is classified as an integrative bibliographic review with an exploratory character, based on periodicals in the health area such as: Scielo, Google Scholar and Pubmed published between 2003 and 2021, filtered through descriptors, selecting 5 books and 17 articles, used as theoretical basis. Evidencing different positions on the subject, pointing out the emergence of composite resin veneers as an excellent alternative treatment for aesthetic problems in anterior teeth, being the most conservative, with immediate result, which makes it possible to control the color and shape of the restored teeth, resembling each increasingly to enamel and dentin, with low cost, which uses material with adequate thickness for better results, however, it is necessary that principles such as biological space, be unaltered during the procedures, so as not to cause pathological changes. The use of composite resin veneers can impact periodontal tissue, requiring a detailed evaluation, mastering the technique and respecting existing protocols, maintaining a minimum gingival margin of 3 mm, so as not to cause gingival inflammation and periodontal sequelae.